Coupling Water‐Proof Li Anodes with LiOH‐Based Cathodes Enables Highly Rechargeable Lithium–Air Batteries Operating in Ambient Air. Issue 4 (11th December 2021) - Lei, Jiang; Gao, Zongyan; Tang, Linbin; Zhong, Li; Li, Junjian; Zhang, Yue; Liu, Tao
Abstract: Realizing an energy‐dense, highly rechargeable nonaqueous lithium–oxygen battery in ambient air remains a big challenge because the active materials of the typical high‐capacity cathode (Li2 O2 ) and anode (Li metal) are unstable in air. Herein, a novel lithium–oxygen full cell coupling a lithium anode protected by a composite layer of polyethylene oxide (PEO)/lithium aluminum titanium phosphate (LATP)/wax to a LiOH‐based cathode is constructed. The protected lithium is stable in air and water, and permits reversible, dendrite‐free lithium stripping/plating in a wet nonaqueous electrolyte under ambient air. The LiOH‐based full cell reaction is immune to moisture (up to 99% humidity) in air and exhibits a much better resistance to CO2 contamination than Li2 O2, resulting in a more consistent electrochemistry in the long term. The current approach of coupling a protected lithium anode with a LiOH‐based cathode holds promise for developing a long‐life, high‐energy lithium–air battery capable of operating in the ambient atmosphere. Abstract : A highly rechargeable lithium‐air battery operating directly in ambient environment is successfully demonstrated by coupling a LiOH‐based cathode and an air‐stable lithium anode with a composite protective layer. Key advantages of the system include: 1) outstanding electrochemical stability; 2) Li dendrite‐free; 3) superior resistance to humidity (99%) and CO2; 4) being applicable to highly wet electrolytes (up to 50vol%).